Discovering miRNA Regulatory Networks in Holt–Oram Syndrome Using a Zebrafish Model - D’Aurizio, Romina; Russo, Francesco; Chiavacci, Elena; Baumgart, Mario; Groth, Marco; D’Onofrio, Mara; Arisi, Ivan; Rainaldi, Giuseppe; Pitto, Letizia; Pellegrini, Marco (Frontiers in Bioengineering and Biotechnology, 2016)
microRNAs (miRNAs) are small non-coding RNAs that play an important role in the post- transcriptional regulation of gene expression. miRNAs are involved in the regulation of many biological processes such as differentiation, apoptosis and cell proliferation. miRNAs are expressed in embryonic, postnatal, and adult hearts and they have a key role in the regulation of gene expression during cardiovascular development and disease. Aberrant expression of miRNAs is associated with abnormal cardiac cell differentiation and dysfunction. Tbx5 is a member of the T-box gene family which acts as transcription factor involved in the vertebrate heart development. Alteration of Tbx5 level affects the expression of hundreds of genes. Haploinsufficiency and gene duplication of Tbx5 are at the basis of the cardiac abnormalities associated with Holt-Oram syndrome (HOS). Recent data indicate that miRNAs might be an important part of the regulatory circuit through which Tbx5 controls heart development. Using high-throughput technology we characterized genome-widely the miRNA and mRNA expression profiles in WT and Tbx5 depleted zebrafish embryos at two developmental time points, 24 and 48 hours post fertilization (hpf). We found that several miRNAs which are potential effectors of Tbx5 are differentially expressed, some of them are already known to be involved in cardiac development and functions, such as miR-30, miR-34, miR-190, miR-21. We performed an integrated analysis of miRNA expression data with gene expression profiles to refine computational target prediction approaches by means of the inversely correlation of miRNA-mRNA expressions. Interestingly these targets have roles in cardiac contractility, cardiomyocyte proliferation/apoptosis and valve formation which are crucial functions regulated by Tbx5. This approach allowed to discover complex regulatory circuits involving novel miRNAs and protein coding genes not considered before in the HOS such as miR-34a and miR-30 and their targets.